Resting state fMRI correlates of Theory of Mind impairment in amyotrophic lateral sclerosis. (December 2017) - Trojsi, Francesca; Di Nardo, Federica; Santangelo, Gabriella; Siciliano, Mattia; Femiano, Cinzia; Passaniti, Carla; Caiazzo, Giuseppina; Fratello, Michele; Cirillo, Mario; Monsurrò, Maria Rosaria; Esposito, Fabrizio; Tedeschi, Gioacchino
Abstract: Theory of Mind (ToM), the ability to recognize thoughts and emotions of another, may be one of the cognitive domains affected in amyotrophic lateral sclerosis (ALS), a neurodegenerative disease now recognized as a multi-system disorder. The present study aimed to identify early dysfunctions of brain resting state functional magnetic resonance imaging (RS-fMRI) networks in a group of ALS patients longitudinally explored for impairment of "cognitive" and "affective" ToM subcomponents. RS-fMRI connectivity was investigated in a group of 21 patients with ALS (i.e., 9 with bulbar-onset or ALS-B and 12 with limb-onset or ALS-L) in early stages of disease and 15 healthy controls (HCs). The same subjects were assessed, at baseline and after six months, for neuropsychological performances, including cognitive and affective ToM and multi-domain cognitive functions. The RS-fMRI study showed a decreased connectivity in frontotemporal areas within the main cognitive resting state networks, including the default mode (DMN), the right and left fronto-parietal (R-, L-FPN), and the salience (SLN) networks, in the entire ALS group. As exploratory results, comparing the ALS-B subgroup to the ALS-L one, we revealed a widespread decrease of RS-fMRI signals in the left middle frontal gyrus for L-FPN and SLN and in the left superior frontal gyrus for SLN. At baseline, no ToM or other cognitive abnormalities were reported in the entire group of ALS patients compared to HCs, although, after six months, the ALS-B subset exhibited a significant impairment of both affective and cognitive ToM subcomponents, whereas the ALS-L group showed significant impairment of the cognitive subcomponent alone. Our findings provide original evidence of the deficit of both ToM subcomponents during the ALS course, supporting the hypothesis of a biologically more aggressive character of ALS-B. Moreover, early RS-fMRI abnormalities in cognitive networks may underlie and precede the clinical appearance of ToM alterations in ALS.